2022
DOI: 10.3390/ejihpe12090097
|View full text |Cite
|
Sign up to set email alerts
|

The Athletic Identity Measurement Scale: A Systematic Review with Meta-Analysis from 1993 to 2021

Abstract: Sport psychology embraced the study of athletic identity in the 1990s. The Athletic Identity Measurement Scale (AIMS) is at the forefront of athletic identity measurement. This quantitative review examined two hypotheses: individual who are most engaged in sports identify most as athletes and thus score higher on the AIMS, and athletic identity relates to positive (e.g., intrinsic motivation) and negative (negative emotions) factors. In addition to our two hypotheses, we explored whether the AIMS subscales inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 93 publications
(67 reference statements)
1
15
1
Order By: Relevance
“…(v) Research shows that a very strong sporting identity, especially if it marginalizes other identities and values (for example, regarding education), is often associated with increased risks for the person ( 103 , 104 ). Future studies on dual careers in women's soccer should therefore directly analyze the influence of Athletic Identity ( 105 , 106 ) on education-related decisions by operationalizing and surveying Athletic Identity in the survey instrument Brewer. (vi) Vocational or academic education are intertemporal allocation decisions.…”
Section: Discussionmentioning
confidence: 99%
“…(v) Research shows that a very strong sporting identity, especially if it marginalizes other identities and values (for example, regarding education), is often associated with increased risks for the person ( 103 , 104 ). Future studies on dual careers in women's soccer should therefore directly analyze the influence of Athletic Identity ( 105 , 106 ) on education-related decisions by operationalizing and surveying Athletic Identity in the survey instrument Brewer. (vi) Vocational or academic education are intertemporal allocation decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted among elite Croatian sprinters and found positive correlations between certain dimensions of engagement (dedication, enthusiasm) and athletic identity. Other positive relationships were highlighted in the meta-analysis by Lochbaum et al [ 22 ] between athletic identity and constructs related to certain dimensions of engagement, such as intrinsic motivation and commitment (constructs close to dedication), positive affect, emotions and feelings (close to enthusiasm), self-esteem, worth, and competence (close to confidence). Among SAs, four studies have shown that athletic identity is positively related to constructs closely associated with sport engagement, such as enthusiastic commitment [ 19 ], achievement [ 43 ] or autonomous [ 44 ] motivation, or intrinsic interest in and value of sport [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous correlates of athletic or academic identity have been documented (i.e., variables that may have reciprocal causality with identity), with associations whose effect sizes are generally small to moderate [ 22 ]. For example, several studies have confirmed Brewer et al’s [ 8 ] hypothesis that athletes competing at elite and advanced levels should endorse a higher athletic identity than those competing at lower levels [ 5 , 6 , 20 ]; for reviews see [ 7 , 22 ]. Reaching international or Olympic levels requires a greater commitment of time, energy and resources than reaching lower levels.…”
Section: Introductionmentioning
confidence: 99%
“…The current return-to-sport criteria primarily emphasize physical measures of readiness; however, psychological measures of rehabilitation, such as athletic identity, may also be valuable due to the influence of injury and rehabilitation on these metrics ( Lochbaum et al, 2022 ). For example, depressive symptoms and loss of motivation over rehabilitation, which lead to worsened physical function, may be increased in those with high athletic identity ( Christino et al, 2015 ; Morgan et al, 2020 ; Renton et al, 2021 ), particularly high athletic identity youth ( Manuel et al, 2002 ; Chow et al, 2016 ; McKay et al, 2019 ; Edison et al, 2021 ; Nyland and Pyle, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…As physical function and psychological recovery from situational change appear to be related to athletic identity, it may be beneficial to gain an understanding of this characteristic over the course of rehabilitation ( Edison et al, 2021 ; Lochbaum et al, 2022 ). However, the literature primarily provides data for athletic identity at pre-injury or immediately post-injury.…”
Section: Introductionmentioning
confidence: 99%